Design and construction of a customizable phantom for the characterization of the three‐dimensional magnetic resonance imaging geometric distortion - Tarraf Torfeh (14776909) (2023)
Design and construction of a customizable phantom for the characterization of the three‐dimensional magnetic resonance imaging geometric distortion Other Information Published in: Journal of Applied Clinical Medical Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/acm2.13462